Tecnologia assistiva: uma pesquisa sobre o acesso ao mercado de trabalho de pessoas portadoras de necessidades especiais na cidade de Araguaína-TO. - Santos, Maria Elisangela Chaves dos (Universidade Federal do Tocantins, 2020)
For many years people with disabilities were discriminated by society, even by their own family. Only then despite many struggles and demands that public is gradually being recognized and valued by society. This article aimed to investigate how people with disabilities realize accessibility to the labor market with the use of Assistive Technology (TA’s) in the city of Araguaína-TO. The study also ranks as a qualitative approach, using the case study, with six (6) Special Needs People (PNE’s) three (3) those who work in the labor market and three (3) who are unemployed in the intention to meet the challenges faced by them. For the results, it was realized that PNE’s feel completely unassisted and without insertion opportunities in the labor market. It was also found that companies do not effectively provide TA resources needed to PNE’s, noting that often companies only hire them to carry out the enforcement of the law that requires them to reserve places for disabled people.